Penatalaksanaan Holistik Penyakit Paru Obstruktif Kronis Dengan Riwayat Tuberkulosis Paru Pada Lansia Perokok - Purnama Simbolon; Diana Mayasari (CV. Jasa Sukses Abadi, 2020)
Chronic Obstructive Pulmonary Disease is a chronic lung disease that can be prevented and treated, which is characterized by air flow resistance that is not completely reversible. COPD in Southeast Asian countries is estimated at 6.3% with the highest prevalence found in Vietnam (6.7%) and China (6.5%). While in Indonesia, according to data from the Basic Health Research (RISKESDAS) 2018, the national smoking prevalence for people aged ≥ 10 years is 28.8% and for aged 10-18 years is 9,1 %. Pulmonary tuberculosis (TB) is a contagious infectious disease caused by Mycobacterium tuberculosis and most often manifests in the lungs. In Indonesia, TB is a major public health problem. The number of TB patients in Indonesia is the 3rd largest in the world. The study conducted was a case report. Primary data was obtained through history taking and physical examination by making home visits, filling family folders, and filling patient files. The assessment is carried out based on a holistic initial diagnosis, process, and end of the visit quantitatively and qualitatively. Patients were diagnosed with COPD from the history taking and physical examination. As well as supporting examinations. Patients do not have enough knowledge of the disease they are suffering from. Patients have a habit of smoking one pack per day. In the patient's environment there are neighbors who are taking TB packages. The patient's work environment is exposed to smoke from burning trash and dust when sweeping the yard. In the evaluation found an increase in patient compliance to avoid risk factors and family knowledge about the disease and the existence of support in carrying out breathing exercises in patients.